2021
DOI: 10.1021/acs.inorgchem.1c01142
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Mediated Photophysics Adjustability in Bis-tridentate Ir(III) Complexes and Their Application in Efficient Optical Limiting Materials

Abstract: A family of novel bis-tridentate Ir­(III) complexes (Ir1–Ir5) incorporating both functional N∧C∧N-type ligands (L1–L5) and N∧N∧C-type ligand (L0) were synthesized attentively and characterized scientifically. The crystalline structures of Ir1, Ir3 and Ir4 were resoundingly confirmed by XRD. With the aid of experimental and theoretical methods, their photophysical properties at transient and steady states were scientifically investigated. The broadband charge-transfer absorption for these aforementioned Ir­(III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Combining the above appealing characteristics, octahedral Ir( iii ) complexes displaying optical power limiting (OPL) properties are of great theoretical and practical value due to the special triplet-state properties, such as strong excited-state absorption (ESA), high triplet quantum yields, and long triplet lifetimes. 18–21…”
Section: Introductionmentioning
confidence: 99%
“…Combining the above appealing characteristics, octahedral Ir( iii ) complexes displaying optical power limiting (OPL) properties are of great theoretical and practical value due to the special triplet-state properties, such as strong excited-state absorption (ESA), high triplet quantum yields, and long triplet lifetimes. 18–21…”
Section: Introductionmentioning
confidence: 99%
“…Because the ESA is more powerful than the GSA, the reverse saturable absorption (RSA—the absorptivity of these complexes would heighten as the incoming light intensity increased) process occurs, which is one of the nonlinear absorption (NLA) behaviors [ 15 , 16 , 17 , 18 ]. In this respect, it has been reported that numerous Ir(III) complexes can be used as effective RSA materials [ 19 , 20 ]. The charge transfer (CT) driven by the D-π interaction between the metal and the chelating ligand is also of benefit to the NLA response [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The charge transfer (CT) driven by the D-π interaction between the metal and the chelating ligand is also of benefit to the NLA response [ 14 ]. Traditional Ir(III) complexes involving three bidentate ligands have been extensively researched in the field of optical power limiting (OPL) performance, due to their extreme synthetic versatility and tunable triplet excited properties [ 20 , 21 ]. Although the interest in tris-bidentate Ir(III) complexes is certainly increasing, these complexes suffer from unsatisfactory stability, causing by the poor resistance of bidentate chelate for undergoing metal–ligand dissociation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the strong spin–orbit coupling (SOC) of these organometallic complexes enhanced by heavy transition metal centers, a electroluminescence device based on such phosphorescence emitting materials can theoretically achieve a unity internal quantum yield compared to the 25% limit enforced for fluorescent molecules . Most studies on these phosphorescent emitters have focused on d 8 square planar triplet emitters of Pt­(II) and d 6 octahedral complexes of ruthenium­(II), osmium­(II), and iridium­(III). Among of them, coordinatively unsaturated platinum­(II) complexes are of particular interest because of their distinctive spectroscopic and luminescent properties. Nevertheless, the square planar geometry of platinum­(II) can form significant intermolecular stacking and thereby induce the formation of unpredictable excimers, which often manifest in a bathochromic shift of the maximum emission wavelength and a reduction of emission quantum yield .…”
Section: Introductionmentioning
confidence: 99%